Starch-Based Electrospun Nanofibrous Scaffold Incorporated With Bioactive Compound From Cayratia Trifolia Promotes Wound Healing By Activating Vegf And Pdgf Signaling Pathways (Applied Biological Research, 2023)
This study focused on the development of starch-based nanofibrous scaffolds  incorporated with linolenyl alcohol derived from ethanolic extracts of Cayratia  trifolia to enhance wound healing. Electrospun nanofibers were fabricated by  blending different concentrations of linolenylalcohol (10, 20, and 40% v/v) with  starch solutions. The resulting nanofibers were characterized for their  morphology, size distribution, thermal stability, FT-IR spectra, and wound  healing properties. The nanofibers loaded with linolenyl alcohol exhibited  diameters ranging from 73 to 95 nm. Further, these nanofibers displayed  improved thermal stability compared to free linolenyl alcohol. FT-IR analysis  confirmed the interaction between starch and linolenyl alcohol. When 40%  linolenyl alcohol-loaded nanofibers were applied,HaCat cells exhibited  increased viability. Western blot analysis revealed elevated levels of vascular  endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF)  expression, suggesting that the developed nanofibers have the potential to  promote angiogenesis and cell proliferation, thus facilitating wound healing. In  conclusion, our study demonstrated that electrospun starch-based nanofibrous  scaffolds incorporating linolenyl alcohol can effectively accelerate wound  healing by activating VEGF and PDGF signaling pathways.
Keywords: Electrospinning; linolenyl alcohol; PDGF; starch; VEGF; wound healing